Rekonstruksi Tujuan Pendidikan Islam Berbasis Taksonomi Transenden - Fuad, Ah. Zakki (ISLAMICA: Jurnal Studi Keislaman, 2015)
This article focuses on the reconstruction of the objective of Islamic education based on transcendent taxonomy. This study is based on the idea that âthe objective of Islamic education is to make students goodâ. The word âgoodâ becomes the key as well as the entrance to formulate the objective of Islamic education by examining the concept of âgoodâ in the QurâÃ¢n. The concept is studied using a model of thematic tafsir (mawdÃ»âÃ®) approach. Using this approach, the word âgoodâ is sought through three stems, i.e., the words ahsan-yuhsin, saluh-yasluh, and khayr with their various forms and changes in the QurâÃ¢n. The classification of verses uses the theory of taxonomy. This article reveals that the objectives of Islamic education taxonomy can be called the âtranscendent taxonomy.â The objectives of Islamic education based on the Qurâan can be classified into three dimensions: ilÃ¢hÃ®yah (theocentrism; divinity), insÃ¢nÃ®yah (anthro-pocentrism; humanity), and kawnÃ®yah (cosmocentrism; naturality).